Porous Silicon Nanoparticles Conjugated Magnetite-Chitosan Graphene Oxide Nanoparticles for Effective Removal of Complex Pollutants - Qu, Xiangmeng (WILEY-V C H VERLAG GMBH, 2025)
The effective removal of complex pollutants is extremely challenging for environmental and material science, especially pollutants including detergents and pesticides do not decompose or degrade in the aquatic environment which cannot be easily removed. Here, a novel biocompatible superparamagnetic nanocomposite integrating the advantages of porous silicon nanoparticles is developed, the chelation ability of chitosan, and graphene-oxide-iron that can simultaneously adsorb complex hydrophobic and hydrophilic pollutants on their internal and external surfaces which have significantly improved pollutant removal efficiency over the current existing methods. A porous silicon nanoparticle (PSi) conjugated magnetite-chitosan-reduced graphene oxide (MCRGO) nanoparticles (PSi-MCRGO) are synthesized for complete removal of detergent, pesticide, and toxic heavy metals cadmium and lead ions from water at a favorable room temperature. The adsorption behavior of the nanocomposites fits well with the Freundlich isotherm and pseudo-second-order kinetics model by adsorption mechanism. Moreover, the fresh and recycled nanocomposites are easily separated by an external magnetic field for reusability due to super magnetite response and show high binding capacity for toxic heavy metal ions. Furthermore, the nanocomposites are biocompatible and reusable, and for the fourth time, recycled nanocomposites can completely remove toxic heavy metals. Overall, the novel nanocomposites completely remove complex pollutants which hold great potential for real water treatment.